DESIGN AND BUILD SCHEDULING INFORMATION SYSTEM FOR RSUD DR. RM. DJOELHAM - Nurullah Husufa; Kenny Hizkia Egianta Ginting; Solusi Fati Krisna Waruwu; Noor Albaqi Virginia (Jurnal TAM (Technology Acceptance Model), 2023)
Hospitals are institutions that provide complete individual health services, which provide facilities in the form of inpatient, outpatient and emergency services. Currently scheduling at RSUD Dr. RM. Djoelham has constraints related to service management that is not optimal, causing delays, this is related to an erratic schedule that makes shift changes that occur not optimal. Genetic algorithms can be used to help schedule employees RSUD Dr. RM. Djoelham automatically. Scheduling automation can be accomplished by properly coding into chromosomes. To realize the management information system RSUD Dr. RM. Djoelham can use the PHP CodeIgniter framework. The purpose of designing a management information system at the hospital is expected to facilitate data collection on employee schedules and speed up schedule data collection. And can minimize the possibility of errors that occur during the scheduling process. The results of this study the system can schedule automatically, making schedules can also be done for each division. Functional testing is carried out using a black box where the test results show that all features can run as they should.